Islam and politics in the contemporary world - Milton-Edwards, Beverley (polity, 2004)
"The dreadful events of 11 September have brought Islam to the forefront of world politics. This book provides an introduction to Islamic politics for those coming to the subject for the first time. This account provides a detailed insight into the many dimensions of Muslim political life; from democracy to despots, from women to world affairs and from history to heresy." "Milton-Edwards offers an account of key contemporary concepts and debates that focus on the relationship between Islam and such topical issues as protest and opposition, violence, the West, democracy, the state and women. In addition the author includes a range of first-hand interviews with major Islamic figures and leaders of movements. Milton-Edwards charts the development of politics in Islam throughout the twentieth century and explores its myriad features. The author also explores the prospects for political Islam in the new millenium." "Islam and Politics in the Contemporary World will be valuable as a textbook for students of politics and religion."--Jacket.